Efficacy and safety of a sublingual buprenorphine/naloxone rapidly dissolving tablet for the treatment of adults with opioid dependence: A randomized trial. Issue 4 (1st October 2016) - Webster, Lynn; Hjelmström, Peter; Sumner, Michael; Gunderson, Erik W.
ABSTRACT: This prospective, randomized, active-controlled, non-inferiority study evaluated the efficacy and safety of a sublingual buprenorphine/naloxone rapidly dissolving tablet (Zubsolv ® ; buprenorphine/naloxone rapidly dissolving tablet) versus generic buprenorphine for induction of opioid maintenance among dependent adults. The study, conducted at 13 sites from June 2013 to January 2014, included a 2-day blinded induction phase and a 27-day open-label stabilization/maintenance phase. During the blinded induction, patients received fixed doses of buprenorphine/naloxone rapidly dissolving tablets or generic buprenorphine. During open-label stabilization/early maintenance, all patients received buprenorphine/naloxone rapidly dissolving tablets. The primary efficacy assessment was treatment retention at day 3; buprenorphine/naloxone rapidly dissolving tablets were considered non-inferior to generic buprenorphine if the lower limit of the 95% confidence interval for the difference between the treatments was ≥–10% in patients retained on day 3. Secondary assessments included opioid withdrawal symptoms and cravings as measured using the Clinical Opiate Withdrawal Scale, the Subjective Opiate Withdrawal Scale, and the opioid cravings visual analogue scale. Safety was also assessed. A total of 313 patients were randomly assigned to induction with generic buprenorphine or buprenorphine/naloxone rapidly dissolving tablets. The mean age was 38.4 years, and the mean duration of opioid dependence was 12.4 years. For the primary efficacy assessment, 235 of 256 patients (91.8%) were retained at day 3 and continued to the maintenance phase. The lower limit of the 95% confidence interval was −13.7; thus, buprenorphine/naloxone rapidly dissolving tablets did not demonstrate non-inferiority to generic buprenorphine, and significantly more patients who received induction with generic buprenorphine (122/128 [95.3%]) were retained at day 3 compared with those who received induction with buprenorphine/naloxone rapidly dissolving tablets (113/128 [88.3%]; 95% confidence interval: −13.7, −0.4; p = 0.040). The rates of clinical response, as measured by the Clinical Opiate Withdrawal Scale, the Subjective Opiate Withdrawal Scale, and the visual analogue scale, were comparable among patients regardless of the induction medication. Treatment with buprenorphine/naloxone rapidly dissolving tablets was generally safe and reduced the severity of withdrawal symptoms and cravings.